A canine case with cystic meningioma showing miraculous reduction of the cystic lesion - WADA, Masae (J Vet Med Sci, 2015)
A 12-year-old spayed female Labrador retriever was presented with forebrain signs. Brain MRI revealed a huge cystic lesion with the thickened falx in the frontal region. The brain parenchyma surrounding the lesion showed significant signs of a mass effect and also increased intracranial pressure. However, the dog suddenly became lucid after about two weeks, and an MRI scan one month after the initial study revealed a dramatically shrunken cystic lesion. The dog survived for over a year until it was euthanized for other reasons, and the brain lesion was diagnosed as a cystic meningioma histologically. To the authors’ knowledge, this is the first report that described the reduction of the cystic lesion of a cystic meningioma in dogs.